Potensi Shopeepay Sebagai Teknologi Pembayaran Untuk Mendukung Inklusi Keuangan: Pendekatan Model UTAUT (Unified Theory of Acceptance and Use of Technology) - Andiani, Diva Nur; Sari, Shinta Permata (Universitas Sains dan Teknologi Komputer, 2024)
Technological advancements have had a significant impact on facilitating financial transactions, one of which is through the use of digital payment systems. ShopeePay, as one of the e-wallets that has rapidly grown in Indonesia, offers convenience in making cashless transactions. Although ShopeePay is becoming increasingly popular, several factors still influence the behavior of its use, particularly among Generation Z. This study aims to analyze the factors that affect ShopeePay usage behavior among Generation Z students at the Universitas Muhammadiyah Surakarta using the UTAUT model. The sampling method used is convenience sampling. This quantitative research uses primary data collected through an online questionnaire via a Google Form link. A total of 275 respondents are involved in the study. Data analysis is conducted using the Smart PLS application. The results of the study indicate that performance expectancy, social influence, and facilitating conditions have affect use behavior, while effort expectancy does not have use behavior. This study emphasizes the importance of performance, social, and infrastructure support aspects in enhancing the acceptance of ShopeePay as a digital payment technology.